WORK SAFETY IN AGRICULTURAL PACKING HOUSES - Martins, M.A.; Abrahão, R. F.; Tereso, M. J. A. (Revista Brasileira de Engenharia de Biossistemas, 2017)
This research’s main objective was the identification of the risk factors of labour (work-related) accidents in packing houses. The research was developed using six representative different packing houses in Campinas, state of São Paulo – Brazil, region. Open and semi-structured interviews, photographed and filmed registers, direct observations and systematic observations of tasks had been carried through. The EWA application allowed the understanding of the workers’ difficulties, relative to aspects of workplace safety, analyzed in lieu of Labour Laws (NR) and Brazilian Standard 5413 (NBR). The risks were classified in Physical, Chemical, Biological, Ergonomic and of Accident. For each identified risk, were presented the possible consequences and suggestions. As a product of this work, it was built a detailed checklist, containing many objective questions, relative to the aspects of workplace safety in tomato processing unities.